Evidentials and relevance - Ifantidou, Elly (Pragmatics & beyond, 2001)
This book uses Sperber and Wilson's Relevance Theory to show how evidential expressions can be analysed in a unified semantic/pragmatic framework. The first part surveys general linguistic work on evidentials, presents speech-act theory and examines Grice's theory of meaning and communication with emphasis on three main issues: for linguistically encoded evidentials, are they truth-conditional or non-truth-conditional, and do they contribute to explicit or implicit communication? For pragmatically inferred evidentials, is there a pragmatic framework in which they can be adequately accounted fo.